ONOMATOPE YANG MENGGAMBARKAN PERASAAN MANUSIA (GIJOUGO) PADA KOMIK ONLINE DORAEMON VOL 1-45” - Erpina Kristin Tambunan Kristin Tambunan; Nana Rahayu Rahayu; Zuli Laili Isnaini Laili Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : In Japanese language, there is word called onomatopoiea or artificial sounds made of an object or living things sounds deprived of the vocabularies which are frequently used either in daily conversations or various media. The example of the artificial sounds of non-living things are jabujabu (artificial sounds and action of splashing water) and barabara (artificial sounds of the hailstone or acorns falling to the ground); and the example of artificial sounds of the living things are: nikoniko (artificial sounds of someone smiling happily), and dokidoki (artificial of pounding heart ) etc. The feeling artificial sounds are usually called gijougo. This research aims to describe the variation of using gijougo to in daily life. This research uses Japanese onomatopoeia which describe feeling (gijougo) as background study and emotion sign; and descriptive as the resesarch method. The data is collected  through comprehensive reading of Doraemon volume 1-45 and classified based on http://nihonjiten.com/nihongo/giongo/. Data is analyzed by comprehending the story context of Doraemon 1-45 to find out the cognitive meaning. From the research, the use, the form, and the meaning of gijougo can be determined. Key words: onomatope, gijougo, artificial sound